(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Lillian Hellman has treated subjects which are vital to every generation in her plays, and marriage is indeed one such vital issue. Her basic concern is with the essential realities of human life. She felt impelled to point out with great vehemence that America was in dire need of change, suffering from a variety of ills which needed to be rectified. She felt a nostalgia, a need to reaffirm old and tried values, a sense of anguish and a feeling of impotence in the face of economic chaos. Hellman was not engaged so much with her times as with the family of man. Her plays are primarily family plays, plays where the sympathy or the lack of it amongst members of the same family, the intervening facts of personal greed, the animosity which may creep into the husband-wife relationship, the ideological stances — all play an important role. A family is a social unit based upon legal (marriage) and on blood (birth) relationships. But is not an enclosed unit insulated from the influence of society.It is moulded, supported, disrupted by social and economic factors and of this Hellman was very conscious.